The Effect of Audit Delay, Company Size, and Public Accounting Firm (KAP) Size on Auditor Switching (Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange for the Period 2019-2023) - Rachmawati, Amartia; Iskandar, Diah (Countable (Contemporary Business and Sustainability Science), 2024)
This study examines the effect of audit delay, company size, and KAP size on auditor switching, with the object of research in banking companies. Auditor switching is carried out by companies to maintain auditor independence in order to produce quality audit results. The purpose of this study is to empirically test the effect of audit delay, company size, and KAP size on auditor switching in banking companies. The population of this study includes banking companies listed on the Indonesia Stock Exchange with a purposive sampling approach which resulted in a sample of 39 companies. Data collection was carried out using secondary data sourced from the annual reports of banking companies listed on the Indonesia Stock Exchange for the period 2019 to 2023 and other official sources, and the data analysis method is logistic regression analysis using SPSS Statistics 25 software. This study concludes that Audit delay has no effect on auditor switching, Company size has a negative effect on auditor switching, and KAP size has no effect on auditor switching.